25 taon tungo sa intelektwalisasyon ng Filipino 25 piling sanaysay sa ekonomiks - Tullao, Tereso S. Jr (Manila De La Salle University Publishing House, 2012)
On economic conditions in the Philippines.
Includes bibliographical references and index.
Keywords: Economics -- Political aspects -- Philippines; Philippines -- Economic conditions